النثر الفني في كتابات عبد الحميد بن باديس وأثره الإصلاحي - مسعودي مباركة; بالي منى; خلوط نعيمة; هاجر احثريب (University of Eloued جامعة الوادي, 2025)
the artistic prose of Abdul Hamid Ibn Badis was distinguished by combining the aesthetic of style and the depth of meaning, as it was not just a means of expressing ideas, but as an effective tool in his reform project .this prose was characterized by clarity, statement, boldness and strength, which gives his writings a special splendor and ability to persuade, in addition to the rhetorical images employed consciously to serve the meaning and manifest it without cost or excessive overshadowing the basic idea.He draws his concepts and ideas from the Holy Quran, the Sunnah of the prophet and the heritage of the righteous ancestor, which gave his writings depth and originality and established their authenticity in the souls of Algerians .
مذكرة ليسانس.دراسات ادبية.2025
Keywords: عبد الحميد بن باديس – اصلاحاته – آثاره Abdul Hamid bin Badis-his reforms-effects